Vocabulary, Language, Prediction (VLP) to Enhance Students’ Reading Achievement in Recount Text - Prayogi Bagas Andriyanto; Linda Dengah (Budapest International Research and Critics University, 2022)
Reading comprehension plays important role for the readers to entertain and gain some information. To scaffold students’ reading comprehension in recount text, the teacher-researcher needs to do pre-reading activity. VLP (Vocabulary, Language, Prediction) is an appropriate strategy to improve students’ reading achievement by mastering vocabulary prior to main reading activity. The students in grade X of SMA that have low English reading achievement were taught English, especially reading comprehension in recoun text. The VLP strategy was applied. Before the VLP strategy applied, the average score was 41.1. The Classroom Action Research was done and VLP strategy was applied. The average score in the first cycle post-test was 67.5, therefore the strategy must be revised and the cycle must be repeated. Then, in the second cycle the students got the average score of post-tests on 77.8. Students’ motivation in learning English also increased as well as their self-confidence to express their thought in class discussion.